The effect of C6- to CIO- fatty acids on larval growth and survival of the olive fruit fly Bactrocera oleae (Diptera: Tephritidae) - Manoukas, A. G. (ENTOMOLOGIA HELLENICA, 2000)
The effects of caproic (C6), amino caproic (C6), caprylic (C8) and cupric (CIO) acid on larval performance of the olive fruit fly, Bactrocera oleae (Gmelin) (Diptera: Tephritidae) were investigated. The acids were added to an artificial larval diet at four different concentration levels, during the mixing of its ingredients. Eggs obtained from a colony of olive fruit flies were placed on these diets and on the control. caproic acid depressed significantly egg hatchability, larval survival and larval weight at the dietary level of 0.05 and 0.1 %. In addition, it did not permit eggs to hatch at the level of 0.2%. On the contrary, aminocaproic acid did not depress any of the parameters recorded up to the level of 0.2%. The levels of 0.4 to 1.6% depressed larval survival larval growth and pupal weight and the level of 3.2% did not permit larvae to survive. caprylic acid depressed significantly hatchability, larval survival and number of pupae/g diet at the level of 0.0125% and gave no pupae at the level of 0.1%. Finally cupric acid depressed egg hatchability, larval survival and larval weight from the level of 0.05% and gave no pupae at the level of 0.2%, Adult emergence was not affected by any of the acids tested.